Dynamic focusing of laser driven positron jets by self-generated fields. (21st December 2020) - Kim, J; Link, A; Canning, D; Fitzsimmons, P; Fooks, J A; Kerr, S; Ma, T; Manuel, M J-E; Mariscal, D; Wallace, R; Williams, G J; Willingale, L; et al.
Abstract: Focusing effect of laser-driven positron jets by self-generated target sheath fields has been observed for the first time experimentally and the results are supported by the computational studies. In the experiment, OMEGA EP short-pulse (0.7 ps, 500 J) irradiates mm-size gold targets with a concave back surface and reference flat-surface targets. Both targets exhibited positrons with quasi-monoenergetic energy peaks while targets with concave curvature also showed increased number of positrons at the detector. The data is consistent with hybrid-PIC simulations confirming that the time-varying electric fields driven by electrons escaping from the target significantly change the trajectories of positrons. These simulations show a small radius of curvature on the rear side increases the relative focusing effect and the positrons to electrons ratio in the escaping plasma. For the smallest radius of curvature, positron jets that are up to 10 times denser can be achieved.